2020
DOI: 10.1111/jpn.13391
|View full text |Cite
|
Sign up to set email alerts
|

L‐Carnitine metabolism, protein turnover and energy expenditure in supplemented and exercised Labrador Retrievers

Abstract: L‐Carnitine is critical for protection against bioaccumulation, long‐chain fatty acid transportation and energy production. Energy production becomes important as the body maintains lean mass, repairs muscles and recovers from oxidative stress. The aim was to investigate the effects of supplemented L‐carnitine on protein turnover (PT), energy expenditure (EE) and carnitine metabolism in muscle/serum of Labrador Retrievers. In a series of experiments, all dogs were fed a low‐carnitine diet and sorted into one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Whatever the underlying mechanisms, given that outcomes are worse in dogs and cats with class II obesity, future research should aim to develop treatments and strategies better tailored to such individuals. For example, therapeutic diets could be better formulated to mitigate lean tissue loss, perhaps, by altering protein and amino acid profiles or adding functional ingredients; in this respect, l-carnitine has effects on protein turnover and energy expenditure 39 , and is already included in therapeutic weight loss diets given its positive effects in promoting muscle mass 40 . Pharmaceutical agents could also be considered; licensed drugs were previously available for dogs, such as dirlotapide, which produced significant weight reduction in clinical trials 41 but had side effects, and was eventually withdrawn from the market.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the underlying mechanisms, given that outcomes are worse in dogs and cats with class II obesity, future research should aim to develop treatments and strategies better tailored to such individuals. For example, therapeutic diets could be better formulated to mitigate lean tissue loss, perhaps, by altering protein and amino acid profiles or adding functional ingredients; in this respect, l-carnitine has effects on protein turnover and energy expenditure 39 , and is already included in therapeutic weight loss diets given its positive effects in promoting muscle mass 40 . Pharmaceutical agents could also be considered; licensed drugs were previously available for dogs, such as dirlotapide, which produced significant weight reduction in clinical trials 41 but had side effects, and was eventually withdrawn from the market.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research summarized several mechanisms of action for these effects [3]. One such plausible mechanism is L-carnitine's ability to prevent exercise-induced muscle degradation [9] by improving protein signaling as well as mitigating leakage of cytosolic proteins from the muscle cell [10,11]. Volek and colleagues [5] found that circulating plasma myoglobin and creatine kinase (CK), both markers of muscle damage, were significantly attenuated, and that malondialdehyde, a marker of oxidative stress, returned to resting values at a faster rate with L-carnitine supplementation compared to placebo.…”
Section: Introductionmentioning
confidence: 99%